FAKTOR-FAKTOR YANG MEMENGARUHI AGRESIVITAS PAJAK - Soesanto, Fredi Rama; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2025)
The purpose of doing this is to determine the effect of leverage, firm size, profitability, managerial ownership towards tax aggresiveness. This research uses secondary data from raw material and primary consumers sector companies that is listed on the Indonesian Stock Exchange during the priod of 2019-2021. The sample is selected using purposive sampling and amounted to 51 companies. The data is processed by using SPSS 16. Outputs obtained from this study indicates that leverage does not have a negative influence towards tax aggresiveness. Firm size and managerial ownership do not have a positive influence towards tax aggresiveness. Profitability has a positive influence towards tax aggresiveness.